The effectiveness of museum intervention on parent-child conversations: a meta-analysis - Kupiec, K; Malmberg, L-E; Mathers, S (Taylor and Francis, 2022)
Museums offer great potential for learning, mediated by parent–child conversations. Despite much qualitative research conducting informative observations of family museum interactions, limited experimental work has investigated how to maximize these experiences. Recent studies have begun to quantitatively examine the potential of researcher-facilitated and resource-based interventions to enhance parent–child conversation in the museum context. This meta-analysis synthesized data from all identified experimental studies in this emerging field (n = 9, k = 111). Findings suggest that museum interventions significantly improve parent–child dyadic conversations (g = .43, p < .001). Sub-analyses showed that the most successful interventions were those which targeted parents (rather than the parent–child dyad) and explicitly guided parental use of conversational strategies. Implications for practice are discussed.